Mathematics Problem Solving Ability in Terms of Adversity Quotient in Problem Based Learning Model With Peer Feedback - Naimnule, Maria; Kartono, Kartono; Asikin, Mohammad (Universitas Negeri Semarang, 2020)
This study aimed to describe the ability of students' problem-solving based on adversity quotient. This study is a mixed-method with sequential explanatory design. The subject of the study is the 8th-grade students of SMP Negeri 1 Miomaffo Timur in the school year of 2018/2019 with class VIII A as the experimental class subject to problem-based learning models with peer feedback and class VIII B as the control class subject to discovery learning models. Quantitative data collection was obtained from the test results of the problem-solving ability of material flat side geometry and qualitative data collection was done by interviewing the results of the problem-solving ability tests through a model of problem-based learning with peer feedback. The result revealed that learning model problem based learning with effective peer feedback and a description of problem-solving abilities in terms of adversity quotient in the high, medium and low categories of the problem-based learning model with peer feedback had various results. It is shown from 4 quitter students, there was no high problem-solving ability, 2 students at no medium problem-solving ability and 2 students at low problem-solving ability. From 15 camper students, 6 students have high problem-solving abilities, 7 students have medium problem-solving abilities, and 2 students who have low problem-solving abilities. From 13 climber students, 5 students had high problem-solving abilities, 7 students had medium problem-solving abilities, and 1 student who had low problem-solving abilities.